Pengaruh Pengawasan yang Dilakukan Pimpinan dan Lingkungan Kerja Fisik terhadap Efektivitas Kerja - Mutiara Annisa; Sri Arita (Universitas Negeri Padang, 2022)
This study aims to determine and analyze: 1) the effect of supervision carried out by the leadership on the affectiveness of the employee’s work 2) the influence of the physical work environment on the effectiveness of the employee’s work 3) the influence of supervision carried out by the leadership and the physical work environment of employee work effectiveness. This type of research is descriptive associative. The total sample is determined by using the cluster proportional random sampling with a sample of 80 sample. The data analysis technique used is multiple linear regression analysis technique. Based on this research, it can be concluded that : 1) supervision carried out by the leadership has a significant effect on the work effectiveness of employees at the Departement of Youth and Sports Education in Kampar Regency 2) The Physical work environment has a significant effect on the work effectiveness of employees at the Departement of Youth and Sports Education in Kampar Regency 2) Supervision by the Leader and the physical Work Environment have a significant effect on the Work Effectiveness of Employees at the Departement of Youth and Sports Education in Kampar Regency. Keywords : supervision by leaders, physical work environment, work effectiveness